Degrowth a vocabulary for a new era - D'Alisa, Giacomo; Demaria, Federico; Kallis, Giorgos (New York Routledge, Taylor & Francis Group, 2015)
"We live in an era of stagnation, rapid impoverishment, rising inequalities, and socio-ecological disasters. In the dominant discourse, these are effects of economic crisis, lack of growth or underdevelopment. This book argues growth is the cause of these problems and that it has become uneconomic, ecologically unsustainable and intrinsically unjust"-- Provided by publisher
Introduction: degrowth / Giorgos Kallis, Federico Demaria and Giacomo D Alisa -- Anti-utilitarianism / Onofrio Romano -- Bioeconomics / Mauro Bonaiuti -- Development, critiques of / Arturo Escobar -- Environmental justice / Isabellle Anguelovski -- Environmentalism, currents of / Joan Martinez-Alier -- Metabolism, societal / Alevgül H. Sorman -- Political ecology / Susan Paulson -- Steady state economics / Joshua Farley -- Autonomy / Marco Deriu -- Capitalism / Diego Andreucci and Terrence McDonough -- Care / Giacomo D Alisa, Marco Deriu and Federico Demaria -- Commodification / Erik Gomez-Baggethun -- Commodity frontiers / Marta Conde and Mariana Walter -- Commons / Silke Helfrich and David Bollier -- Conviviality / Marco Deriu -- Dematerialization / Sylvia Lorek -- Dépense / Onofrio Romano -- Depoliticization ('the political') / Erik Swyngedouw -- Disaster, pedagogy of / Serge Latouche -- Entropy ; Emergy / Sergio Ulgiati -- Gross domestic product / Dan O'Neill -- Growth / Peter A. Victor -- Happiness / Filka Sekulova -- Imaginary, decolonization of / Serge Latouche -- Jevons' paradox / Blake Alcott -- Neo-Malthusians / Joan Martinez-Alier -- Peak-oil / Christian Kerschner -- Simplicity / Samuel Alexander -- Social limits of growth / Giorgos Kallis -- Back-to-the-landers / Rita Calvário and Iago Otero -- Basic and maximum income / Samuel Alexander -- Community currencies / Kristofer Dittmer -- Co-operatives / Nadia Johanisova, Ruben Suriñach Padilla and Philippa Parry -- Debt audit / Sergi Cutillas, David Llistar and Gemma Tarafa -- Digital commons / Mayo Fuster Morell -- Disobedience / Xavier Renou -- Eco-communities / Claudio Cattaneo -- Indignados (Occupy) / Viviana Asara and Barbara Muraca -- Job guarantee / B.J. Unti -- Money, public / Mary Mellor -- New economy / Tim Jackson -- Nowtopians / Cris Carlsson -- Post-normal science / Giacomo D' Alisa and Giorgos Kallis -- Unions / Denis Bayon -- Urban gardening / Isabelle Anguelovski -- Work sharing / Juliet B. Schor -- Buen Vivir / Eduardo Gudynas -- Economy of permanence / Chiara Corazza and Solomon Victus -- Feminist economics / Antonella Picchio -- Ubuntu / Mogobe B. Ramose -- Epilogue: from austerity to depense / Giacomo D'Alisa, Giorgos Kallis and Federico Demaria
Includes bibliographical references and index.
Keywords: Economic development -- Moral and ethical aspects; Stagnation (Economics).; Poverty; Sustainable development